VO#026 Resubmit proposal of steel structure from 6th to 12th storey and above works rev.1 - BUCG-ABC Joint Venture (BUCG-ABC JV) (Brac University, 2023)
This record consists of general correspondence regarding the resubmission of the proposal of steel structure from 6th to 12th storey and above works of BRACU new campus building.